2022
DOI: 10.3390/healthcare10020304
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Dutch Midwives Regarding the Quality of Care during the COVID-19 Pandemic

Abstract: This study assessed how the quality of care during the COVID-19 pandemic has been experienced by Dutch midwives. At the beginning of May 2020, 15 Dutch midwives were interviewed during the first wave of the pandemic. The interviews included questions based on the value-based healthcare framework by Porter. The interviews were transcribed verbatim, coded, and analyzed according to recurrent themes using the directed content analysis approach. Key themes identified included high quality midwifery care, informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Additionally, a study done by Giorgi et al (2020) reported that frontline health workers including midwives experienced a variety of mental health challenges during COVID-19 outbreak including anxiety, depression, post-traumatic stress disorder (PTSD), sleep disorders and fear which may affect the health service utilization which including maternal health services. Similarly, other studies found that the midwives were worried to transmit the infectious (COVID-19) to their family members (Hazfiarini et al, 2021;Hijdra et al, 2022). In line with this, even some pregnant women were scared to be infected with COVID-19, as a result they were decided to have home delivery that might have put them in danger of increased maternal morbidity or mortality.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, a study done by Giorgi et al (2020) reported that frontline health workers including midwives experienced a variety of mental health challenges during COVID-19 outbreak including anxiety, depression, post-traumatic stress disorder (PTSD), sleep disorders and fear which may affect the health service utilization which including maternal health services. Similarly, other studies found that the midwives were worried to transmit the infectious (COVID-19) to their family members (Hazfiarini et al, 2021;Hijdra et al, 2022). In line with this, even some pregnant women were scared to be infected with COVID-19, as a result they were decided to have home delivery that might have put them in danger of increased maternal morbidity or mortality.…”
Section: Discussionmentioning
confidence: 85%
“…For future obstetric care during the pandemic, additional telephone checks and postpartum face-to-face visits are recommended to improve the quality of care. After the pandemic, it is recommended that the midwifery care schedule be restored to its pre-pandemic state (Hijdra et al, 2022). Midwives can help with therapy by talking to a psychiatrist and monitoring pregnant women.…”
Section: Results Article Characteristic Based On Research Designmentioning
confidence: 99%
“…According to a Norwegian white paper on quality of care and patient safety (Meld. St. 11, 2020 with the pandemic (Ardebili et al, 2021;Hijdra et al, 2022). These studies revealed the fear held by the healthcare professionals in being a carrier of the virus and thus infecting patients, colleagues and their own families (Ardebili et al, 2021;.…”
Section: Processmentioning
confidence: 99%